Inactivation as a New Regulatory Mechanism for Neuronal Kv7 Channels - Jensen, Henrik Sindal (The Biophysical Society, 2007)
Voltage-gated K(+) channels of the Kv7 (KCNQ) family have important physiological functions in both excitable and nonexcitable tissue. The family encompasses five genes encoding the channel subunits Kv7.1–5. Kv7.1 is found in epithelial and cardiac tissue. Kv7.2–5 channels are predominantly neuronal channels and are important for controlling excitability. Kv7.1 channels have been considered the only Kv7 channels to undergo inactivation upon depolarization. However, here we demonstrate that inactivation is also an intrinsic property of Kv7.4 and Kv7.5 channels, which inactivate to a larger extent than Kv7.1 channels at all potentials. We demonstrate that at least 30% of these channels are inactivated at physiologically relevant potentials. The onset of inactivation is voltage dependent and occurs on the order of seconds. Both time- and voltage-dependent recovery from inactivation was investigated for Kv7.4 channels. A time constant of 1.47 ± 0.21 s and a voltage constant of 54.9 ± 3.4 mV were determined. It was further demonstrated that heteromeric Kv7.3/Kv7.4 channels had inactivation properties different from homomeric Kv7.4 channels. Finally, the Kv7 channel activator BMS-204352 was in contrast to retigabine found to abolish inactivation of Kv7.4. In conclusion, this work demonstrates that inactivation is a key regulatory mechanism of Kv7.4 and Kv7.5 channels.